2020
DOI: 10.1039/d0ma00475h
|View full text |Cite
|
Sign up to set email alerts
|

Magic-angle spinning NMR spectroscopy provides insight into the impact of small molecule uptake by G-quartet hydrogels

Abstract: Small molecule guests influence the functional properties of supramolecular hydrogels. Molecular-level understanding of such sol-gel compositions and structures is challenging due to the lack of long-range order and inherently heterogeneous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…This scenario is especially likely for aggregates, where interactions of very different natures are involved. In order to test this hypothesis, we carried out high-resolution MAS (HR-MAS) NMR titration experiments 55 with variable spinning frequencies using two different good solvents ( Figure 6 ). Our aim was to monitor the evolution of different noncovalent interactions in solid PBI-1 aggregates at an early stage of solvent-induced disassembly.…”
Section: Resultsmentioning
confidence: 99%
“…This scenario is especially likely for aggregates, where interactions of very different natures are involved. In order to test this hypothesis, we carried out high-resolution MAS (HR-MAS) NMR titration experiments 55 with variable spinning frequencies using two different good solvents ( Figure 6 ). Our aim was to monitor the evolution of different noncovalent interactions in solid PBI-1 aggregates at an early stage of solvent-induced disassembly.…”
Section: Resultsmentioning
confidence: 99%
“…The above results demonstrate that the DPC crosslinking approach incorporating both phototriggered S -nitrosylation and Schiff base reactions occurs at both the small molecule and macromolecular levels. To gain insight about the polymer structure, the 1 H magic-angle spinning (MAS) NMR spectra of the raw materials and the obtained gel were conducted according to the reported method 27 and the results confirmed the changes of polymer local environments caused by gelation (Fig. S15b, ESI†).…”
mentioning
confidence: 80%
“…Interestingly, density functional theory (DFT) calculations were also performed to complement the experimental 11 B NMR data by optimizing the structure of the guanosine-borate monoester and diesters and calculating 11 B NMR shieldings to correlate with the experimentally measured 11 B shifts. These showed that the cis diester form was the preferred one for gelation [26]. This expanded on prior work by Peters et al, who used solid-state 11 B MAS NMR to characterize the guanosine-borate hydrogels.…”
Section: Nmr Spectroscopymentioning
confidence: 80%